TRPV1 Tunes Optic Nerve Axon Excitability in Glaucoma - McGrady, Nolan R.; Risner, Michael L.; Vest, Victoria; Calkins, David J. (Frontiers in Physiology, 2020)
The transient receptor potential vanilloid one (TRPV1) in the central nervous system may contribute to homeostatic plasticity by regulating intracellular Ca2+, which becomes unbalanced in age-related neurodegenerative diseases, including Alzheimer’s and Huntington’s. Glaucomatous optic neuropathy – the world’s leading cause of irreversible blindness – involves progressive degeneration of retinal ganglion cell (RGC) axons in the optic nerve through sensitivity to stress related to intraocular pressure (IOP). In models of glaucoma, genetic deletion of TRPV1 (Trpv1-/-) accelerates RGC axonopathy in the optic projection, while TRPV1 activation modulates RGC membrane polarization. In continuation of these studies, here we found that Trpv1-/- increases the compound action potential (CAP) of optic nerves subjected to short-term elevations in IOP. This IOP-induced increase in CAP was not directly due to TRPV1 channels in the optic nerve, since the TRPV1-selective antagonist iodoresiniferatoxin had no effect on the CAP for wild-type optic nerve. Rather the enhanced CAP in Trpv1-/- optic nerve was associated with increased expression of the voltage-gated sodium channel subunit 1.6 (NaV1.6) in longer nodes of Ranvier within RGC axons, rendering Trpv1-/- optic nerve relatively insensitive to NaV1.6 antagonism via 4,9-anhydrotetrodotoxin. These results indicate that with short-term elevations in IOP, Trpv1-/- increases axon excitability through greater NaV1.6 localization within longer nodes. In neurodegenerative disease, native TRPV1 may tune NaV expression in neurons under stress to match excitability to available metabolic resources.